When social objects collaborate: Concepts, processing elements, attacks and challenges. (February 2017) - Khan, Wazir Zada; Aalsalem, Mohammed Y; Khan, Muhammad Khurram; Arshad, Quratulain
Abstract: Social Collaborative Internet of Things (SCIoT) is a more elaborative form of Social Internet of Things (SIoT) in which, social objects collaborate by interacting and sharing information to achieve a common goal. In order to collaborate, smart objects need to be grouped and work together by developing a trusted environment and cooperative relationships among them. Trust management plays an important role in such SCIoT scenarios where smart objects have to establish social relationships. Also, these smart objects select other objects in their vicinity as friend or foe based on their trust upon those objects to establish an effective successful collaboration. In this paper, we contribute to present a survey of existing trust management schemes for SIoT, compare them by outlining their features and identify their drawbacks, etc. Furthermore, as far as our knowledge is concerned, we are the first to propose the definition of SCIoT, a hierarchical model of SCIoT for its important processes and a few application scenarios. In addition, we present a threat model to categorize the possible attacks that can be launched on SCIoT. Finally, we also highlight some challenges in the SCIoT.